The Relationship of Children's Nutritional Status with the Development of Preschool Age Children - Sanghati, Sanghati (Hasanuddin Medan, 2022)
The most important phase in a child's growth and development is during infancy and toddlerhood, because at that time it will determine the child's future both physically, mentally and behaviorally. One factor that influences development is nutritional status. The aim of this research was to determine the relationship between children's nutritional status and the development of pre-school age children in RT 001 RW 001 Biccoing Village, Tonra District, Bone Regency. The type of research used is analytical research with a cross sectional study approach. The population of this study were pre-school children in RT. 001 RW. 001 Biccoing village, Tonra subdistrict, Bone district in 2014, namely 40 children. The number of samples studied was 40 children using total sampling techniques. Data was collected by filling out a questionnaire and then analyzed using the Chi Square test with a significance level of ? < 0.05. Based on the results of research on nutritional status, it shows that of the 40 respondents, 33 people (82.5%) had good nutritional status, and the majority experienced normal development, namely 31 people (93.9%). However, there are still a small number who experience abnormal development, namely 2 people (6.1%). After carrying out the Chi Square statistical test, the value of p = 0.000 < 0.05 was obtained. Based on the research results, it was concluded that there is a relationship between nutritional status and the development of pre-school age children. It is hoped that health workers will be able to improve services, especially monitoring children's nutritional status and efforts to detect early deviations in children's development on a regular basis, as well as providing health education to the community, especially regarding children's nutritional status.